Why does emissions trading under the EU ETS not affect firms' competitiveness? Empirical findings from the literature - Eugénie Joltreau; Katrin Sommerfeld (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2016)
Environmental policies may have important consequences for firms' competitiveness or profitability. However, the empirical literature shows that hardly any statistically significant effects on firms can be detected for the European Union Emissions Trading Scheme (EU ETS). On the basis of existing literature, we focus on potential explanations for why the empirical literature finds hardly any significant competitiveness effects on firms, least not during the first two phases of the scheme (2005-2012). We also reason why the third phase (2013-2020) could reveal similar results. We show that the main explanations for this finding are a large over-allocation of emissions ertificates leading to a price drop and the ability of firms to pass costs onto consumers in some sectors. Cost pass-through, in turn, partly generated windfall profits. In addition, the relatively low importance of energy costs indicated by their average share in the budgets of most manufacturing industries may limit the impact of the EU ETS. Finally, small but significant stimulating effects on innovation have been found so far. These different aspects may explain why the empirical literature does not find significant effects from the EU ETS on firms' competitiveness.
urn:nbn:de:bsz:180-madoc-414912
Keywords: Q52; Q58; D22; 330; Cap and Trade system; EU ETS; firm-level competitiveness